Bridge over Snake River at Nome, probably 1900 - Warner, Arthur Churchill, 1864-1943 (1900)
In May 1900 the Cape Nome Transportation, Bridge, and Development Company was authorized by Congress to construct a general traffic bridge over the Snake River. Warner 118 Filed in Alaska series.